Content analysis in social and environmental reporting research: trends and challenges. Issue 2 (14th September 2015) - Vourvachis, Petros; Woodward, Thérèse
Abstract : Purpose: – The purpose of this paper is to review the use of content analysis in social and environmental reporting (SER) research. It explores how the relevant literature has evolved over time and particularly how recent developments have affected the validity and reliability challenges that researchers face when executing the method. Design/methodology/approach: – The paper combines a quasi-systematic review of the literature employing content analysis (examining a sample of 251 studies published over the last 40 years in a wide array of journals with interest in the field), with a largely interpretive meta-analysis, using an index, considering the research questions asked and frameworks used as well as the specific content analysis decisions. Findings: – A number of issues of concern in the use of the method are identified, mainly over comparability and reliability of coding schemes. Potential explanations are developed and methodological refinements that could enhance the usefulness of content analysis methods in SER research are subsequently proposed. Research limitations/implications: – It should be acknowledged that, as 251 SER studies have been reviewed, there is always the possibility that some unique studies that could have contributed in the discussion have been ignored. Practical implications: – By reviewing the use of the method in a comprehensive sample of 251 SER studies published over the last 40 years in a wide array of journals with interest in the field, the paper also offers a guide for researchers (particularly in the SER field) wishing to employ content analysis in the future. Originality/value: – The paper contributes to the literature by offering a critical and comprehensive review of the method's theoretical underpinnings and application in SER research, and by describing changing patterns in content analysis, in order to help build a more secure foundation for future work.